Moderating influence of employee engagement on the relationship between union management cooperation activity and employee performance among doctors in public service health sector in Nairobi County, Kenya - Ongiri, Nyakiba Agnes; Muya, James; Matula, Phylisters Daizy (International Journal of Economics, Business and Management Studies, 2024)
The study main objective was to establish the influence of Union Management Cooperation Activity on employee performance among doctors in public service health sector in Nairobi County, Kenya as moderated by employee engagement. The target population was 789 medical doctors and 21 top managers. Stratified sampling technique and simple random sampling to pick 327 doctors while purposive sampling technique was used to pick 21 top managers. The study employed convergent parallel mixed methods design. A self-constructed structured questionnaire was utilized to gather quantitative data from the doctors while interview guide was adopted to collect qualitative data from top management. Quantitative data was statistically analyzed using descriptive (means & standard deviation) and inferential tools (pearson correlation and regression analysis). Qualitative data was thematically analyzed based on objectives and presented in narrative form using text. The study found that union-management cooperation activity had a positive and significant influence on the performance of doctors in public service health sector. Further, results showed that relationships between union-management cooperation activity and employee performance were significantly moderated by employee engagement. The study concluded that union-management cooperation activity was core drivers of employee performance. The study emphasizes the importance of embracing union-management cooperation within organizations. It suggests that both management and trade unions should utilize the study findings to foster cooperation, aligning with the tripartite principle and benefiting all stakeholders involved. The study provides valuable insights for managers explore strategic options for its adoption and implementation as a fundamental aspect of employee management, especially within the healthcare sector.